Improvement of Work Productivity and Quality of Life with Anti-Tumor Necrosis Factor Treatment Used in Crohn’s Disease in Routine Clinical Practice in Turkey - Toruner, Murat; Basaranoglu, Metin; Atug, Ozlen; Senturk, Omer; Akyuz, Filiz; Cekic, Cem; Over Hamzaoglu, Hulya; Tekin, Fatih; Sezgin, Orhan; Akpinar, Hale; Celik, Aykut Ferhat; Tezel, Ahmet; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Patients with Crohn’s disease experience major deterioration in work productivity and quality of life. We aimed to provide the long-term effects of anti-tumor necrosis factor agents on work productivity and activity impairment and quality of life in patients with Crohn’s disease using the Inflammatory Bowel Disease Questionnaire and the Short-Form Health Survey-36.Methods: Patients with Crohn’s disease and initiated an anti-tumor necrosis factor treatment were included and followed up for 12 months in this observational study.Results: A total of 106 patients were included in this study, and 64.2% of the patients were males. Mean [± standard deviation] age was 36.8 [± 10.9] years. At baseline, mostly perianal fistulas [65.7%] were observed [n = 23]. Intestinal stenosis was detected in 34.9% of the patients [n = 37], and most of the stenosis was located in the ileum [70.6%] followed by the colon [20.6%]. Extraintestinal symp- toms were observed in 24 patients [22.6%]. Most frequent extraintestinal symptom was arthritis with 71.4% [n = 15]. Mean time from first symptom to initiation of anti-tumor necrosis factor treatment was 6.3 [± 5.0] years. Improvements in work productivity and activ- ity impairment scores throughout 12 months were −24.1% [P = .003] for work time missed, −18.0% [P = .006] for impairment at work, −8.5% [P = .160] for overall work impairment, and −17.0% [P < .001] for daily activity impairment. Similarly, significant improvements [P < .001] were detected in all components of the Inflammatory Bowel Disease Questionnaire when compared to baseline. Statistically sig- nificant improvements [P < .05] were detected for all components of Short-Form Health Survey-36 except for mental health [P = .095]. Conclusion: Our study indicates the significant improvement in work productivity and activity impairment and quality of life of patients with Crohn’s disease who receive long-term anti-tumor necrosis factor treatment.